ZAP‐70 Genotype Disrupts the Relationship Between Microbiota and Host, Leading to Spondyloarthritis and Ileitis in SKG Mice. Issue 10 (October 2014) - Rehaume, Linda M.; Mondot, Stanislas; Aguirre de Cárcer, Daniel; Velasco, Jared; Benham, Helen; Hasnain, Sumaira Z.; Bowman, Jaclyn; Ruutu, Merja; Hansbro, Philip M.; McGuckin, Michael A.; Morrison, Mark; Thomas, Ranjeny
<x xml:space="preserve">Abstract</x> Objective The spondyloarthritides share genetic susceptibility, interleukin‐23 (IL‐23) dependence, and the involvement of microbiota. The aim of the current study was to elucidate how host genetics influence gut microbiota and the relationship between microbiota and organ inflammation in spondyloarthritides. Methods BALB/c ZAP‐70W163C–mutant (SKG) mice, Toll‐like receptor 4 (TLR‐4)–deficient SKG mice, and wild‐type BALB/c mice were housed under specific pathogen–free conditions. SKG and wild‐type BALB/c mice were maintained under germ‐free conditions, and some of these mice were recolonized with altered Schaedler flora. All of the mice were injected intraperitoneally with microbial β‐1, 3‐glucan (curdlan). Arthritis, spondylitis, and ileitis were assessed histologically. Microbiome composition was analyzed in serial fecal samples obtained from mice that were co‐housed beginning at the time of weaning, using 454 pyrosequencing. Infiltrating cells and cytokines in the peritoneal cavity were measured by flow cytometry and enzyme‐linked immunosorbent assay. Cytokine, endoplasmic reticulum (ER) stress marker, and tight junction protein transcription was measured by quantitative real‐time polymerase chain reaction. Results Microbiota content and response to curdlan varied according to whether T cell receptor signal strength was normal or was impaired due to the ZAP‐70W163C mutation. Curdlan triggered acute inflammation regardless of the presence of the SKG allele or microbiota. However, no or limited microbiota content attenuated the severity of arthritis. In contrast, ileal IL‐23 expression, ER stress, lymph node IL‐17A production, goblet cell loss, and ileitis development were microbiota‐dependent. Ileitis but not arthritis was suppressed by microbiota transfer upon co‐housing SKG mice with wild‐type BALB/c mice, as well as by TLR‐4 deficiency. Conclusion The interaction between immunogenetic background and host microbiota leads to an IL‐23–dependent loss of mucosal function, triggering ileitis in response to curdlan.